The Effect of Guided Inquiry Learning Integrated with SETS on Students' Critical Thinking Ability and Self-Efficacy in Learning Buffer Solutions - Yanti, Widya Ikhma; Suyanta, Suyanta (FKIP - Universitas Riau, 2025)
The low critical thinking ability and self-efficacy of students in learning chemistry are caused by learning approaches that are still teacher-centered, less contextual, and limited opportunities for students to engage in problem-solving activities that require higher-level and reflective thinking. This study aims to analyze the differences in critical thinking ability and self-efficacy between students who participate in guided inquiry learning integrated with SETS and students who participate in scientific approach on buffer solution topic. This study used a quasi-experiment method with a pretest-posttest control group design involving four classes The results showed that the experimental class N-Gain score was higher than the control class, both in critical thinking ability and self-efficacy. The N-Gain score of critical thinking ability in the experimental class was 0.633 (medium category), while the control class was 0.488 (medium category). On the self-efficacy variable, the experimental class obtained an N-Gain score of 0.423 (medium category), while the control class was 0.210 (low category). The MANOVA test results showed that there were significant differences between the two groups in critical thinking ability and self-efficacy. So that the guided inquiry integrated with SETS is proven effective in improving students' critical thinking ability and self-efficacy in buffer solution topic.